Legal Aid System in India and Nepal: An Overview - Singh, T .P.; Vandana, Parihar (Kathmandu School of Law Review, 2013)
Through this Article, an effort is made to understand the existing legal aid system of concerned countries, i.e. India and Nepal. The Constitution of India and the Interim Constitution of Nepal are the sources of social justice and the aim and objective of this Article is to draw focus on them. Both the countries have changed their domestic law to harmonize with international covenants. The co-relation between human rights and the fundamental rights is necessary to a proper social justice. This article assesses the legal aid system of India and Nepal. Legal Aid Act 1997 of Nepal and Legal Service Authority Act 1987 of India are functioning in the forefront but the soul lies in the Constitution of the respective countries. The article presents comparative legal view on the systems. Likewise, the article attempts to find out the strength and weakness of the Legal Aid System and solutions to overcome the shortcoming of the system.